2018
DOI: 10.1038/s41598-018-35638-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyvinyl alcohol (PVA) infiltrated MWCNTs buckypaper for strain sensing application

Abstract: Buckypaper (BP)/polymer composites are viewed as a viable option to improve the strain transfer across the buckypaper strain sensor by means of providing better interfacial bonding between the polymer and carbon nanotubes (CNTs). Multiwall carbon nanotubes (MWCNTs) BP/polyvinyl alcohol (PVA) composites were fabricated by a sequence of vacuum filtration and polymer intercalation technique. The optimized conditions for achieving a uniform and stable dispersion of MWCNTs were found to be using ethanol as a disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 81 publications
0
40
0
Order By: Relevance
“…Nonetheless, few research efforts have been devoted to investigate the effect of biochar produced at high temperatures towards the enhancement of polymer conductivity [29]. This field has conducted in-depth studies 2 of 12 on using thermoset-based composites [30][31][32][33] or carbon nanotubes-based thermoplastic polymeric hosts [34][35][36][37][38] but it has neglected to consider thermoplastic and biochar at the same time. The use of a thermoplastic polymer matrix could be very useful for the production of irreversible resistive sensors that could detect the plastic deformation of the material at lower pressure ranges than thermoset-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, few research efforts have been devoted to investigate the effect of biochar produced at high temperatures towards the enhancement of polymer conductivity [29]. This field has conducted in-depth studies 2 of 12 on using thermoset-based composites [30][31][32][33] or carbon nanotubes-based thermoplastic polymeric hosts [34][35][36][37][38] but it has neglected to consider thermoplastic and biochar at the same time. The use of a thermoplastic polymer matrix could be very useful for the production of irreversible resistive sensors that could detect the plastic deformation of the material at lower pressure ranges than thermoset-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) possess impressive properties, such as a hundred times higher tensile strength than steel, low electrical conductivity, and good thermal conductivity [1,2]. Many researchers have investigated CNTs as pressure sensors [3,4] and strain sensors [5,6] because of their excellent electromechanical properties. Bu et al reported drop-casting-prepared multi-walled CNT films with a sensitivity of 2.5 for the strain below 0.1% [7].…”
Section: Introductionmentioning
confidence: 99%
“…The current method of synthesis has provided a solution to the intrinsic tendency of graphene sheets to agglomerate due to van der Waals forces of attraction, the high viscosity of graphene/polymer suspension, and low solubility in solvents. Whereas, the graphene oxide produced initially had essential functional groups to make strong bonds with polyvinyl alcohol and produced a buckypaper stain sensor with strong interfacial bonding among graphene sheets and polymer matrix 17 . Han, et al 18 synthesized Carbon nanotube-based buckypaper infiltrated with a polymer matrix of epoxy resin that helped to achieve significant mechanical properties such as tensile strength, Young's modulus, and elongation-at-break of 146.1 Mpa, 13.8 GPa, and 1.3% respectively.…”
mentioning
confidence: 99%